Staff perceptions of collaboration on a new interprofessional unit using the Assessment of Interprofessional Team Collaboration Scale (AITCS). Issue 6 (1st November 2016) - Prentice, Dawn; Jung, Bonny; Taplay, Karyn; Stobbe, Karl; Hildebrand, Lisa
ABSTRACT: The aim of this study was to obtain baseline information on staff attitudes and perceptions of interprofessional collaboration on a newly formed interprofessional education unit. The Assessment of Interprofessional Team Collaboration Scale (AITCS) was administered to 54 interprofessional team members on a 30-bed medical interprofessional education (IPE) unit. We found that the team members respected each other but felt they needed more organisational support to further develop team skills. Additionally, team members noted that they did not have enough time for team reflection or to make changes to the team processes. The results obtained from this study will help to develop and refine educational strategies to assist the staff working on the IPE unit.